THE DEVELOPMENT OF A COOPERATIVE LEARNING MANAGEMENT MODEL USING TECHNIQUES TAI TO PROMOTE MATHEMATICS PROBLEM SOLVING SKILLS OF MATHEMATICS MAJORS, FACULTY OF EDUCATION, RAMKHAMHAENG UNIVERSITY - Hanhaw, Samrouy (Journal of Education and Innovation, 2026)
The objectives of this research were to 1) study the problems and needs for developing a cooperative learning management model using the TAI technique to promote students' mathematical problem-solving skills; 2) develop a cooperative learning management model using the TAI technique to promote students' mathematical problem-solving skills; 3) test the cooperative learning management model using the TAI technique to promote students' mathematical problem-solving skills to be effective according to the specified criteria of 80/80; 4) compare the mathematical learning achievement before and after cooperative learning management using the TAI technique of students; 5) study the mathematical problem-solving ability after cooperative learning management using the TAI technique of students compared to the 70% criterion; and 6) study the satisfaction of students with the learning management model. The sample group was 40 mathematics major students in the academic year 2024, Faculty of Education, Ramkhamhaeng University. The researcher determined the appropriate sample size using the G* Power program and used multi-stage sampling. The research tools consisted of 1) a questionnaire on teachers' opinions regarding the problems and needs for developing learning management models, 2) a cooperative learning management plan using the TAI technique, 3) a mathematics achievement test, 4) a mathematics problem-solving ability test, and 5) a questionnaire on satisfaction with the learning management models. The statistics used for analysis were mean, standard deviation, percentage, and t-test (Dependent Samples). The research results found that 1) the problems in developing learning management models Overall, the level of learning management was moderate ( = 3.50, SD = 0.52), and the need to develop the learning management model overall was at a high level ( = 3.51, SD = 0.59). 2) The results of developing the cooperative learning management model using the TAI technique to promote students' mathematical problem-solving skills consisted of 5 components: (1) principles of the learning management model, (2) objectives of the model, (3) learning content, (4) learning management process of the model, consisting of (4.1) problem study step, (4.2) study, learn and analyze content problems by students planning together, (4.3) plan implementation step and lesson summary, and (4.4) testing and evaluation step, and (5) measurement and evaluation of learning outcomes. 3) The results of using the cooperative learning management model using the TAI technique to promote students' mathematical problem-solving skills showed that it was effective at 88.40/83.43, which is higher than the set criteria. 4) The mathematics learning achievement of students who received cooperative learning management using the TAI technique after the learning management was higher than before the learning management. 5) Students' mathematical problem-solving ability after cooperative learning using the TAI technique was significantly higher than 70 percent at the .05 level, and 6) students' satisfaction with the cooperative learning model using the TAI technique to promote mathematical problem-solving skills was at a high level overall.